Desain Ui/Ux Aplikasi Various Wash Services Marketplace Ez Clean Menggunakan Metode Design Thinking - Muh. Ahlun Nazar; Eka Dyar Wahyuni; Agussalim Agussalim (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2024)
In the modern era, various washing services, especially motorbike, car, clothes and shoe washing services, are growing very rapidly. Unfortunately, various wash services, especially motorbike, car, clothes and shoe washing services, are currently still quite ineffective. The aim of this research is to design a various wash services application that produces good usability on an Android-based mobile platform. This research will discuss mobile application interface design using the design thinking method. This method focuses on human interests as users bringing new innovations. The design evaluation stage will be carried out based on recommendations from ISO 9241-11 in measurements. The results of the test after producing the final value from two iterations on twenty washing service providers produced an effectiveness value of 97.25%, efficiency 97.59%, and ten users (buyers) produced an effectiveness value of 97.5%, efficiency 94.14 %, then the aspect of the thirty respondents produced a Satisfaction (SUS) value of 82.83, where the usability results were categorized as good or good